2014
DOI: 10.4018/ijkm.2014100101
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Reasons, Implications and Consequences of Demographic Change for IT Departments in Times of Scarcity of Talent

Abstract: The skill shortage is becoming an ever-increasing challenge for IT departments. Allocation of resources in the best possible way is even more important. The challenge is to improve the enterprise not only on the side of the organizational and process level, but to develop new strategies and approaches in human resource management. Only a symbiosis of the disciplines economics, psychology and information technology will enable relevant and indispensable employees and promote loyalty to the company. A frequent c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
3
2
1

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 44 publications
0
2
0
Order By: Relevance
“…In addition human resources management is a very complex domain on its own and a SLR conducted in March 2014 has shown that the the problem of skill shortage in companies can only be solved if further scientific areas, e.g. psychology, sociology or organization theory are considered as well (Radant, 2014;Radant, Colomo-Palacios, & Stantchev, 2014). This paper shows that the research community currently does not provide satisfactory answers for the problem of scarcity of talent and skill shortage in IT-departments.…”
Section: Discussionmentioning
confidence: 92%
“…In addition human resources management is a very complex domain on its own and a SLR conducted in March 2014 has shown that the the problem of skill shortage in companies can only be solved if further scientific areas, e.g. psychology, sociology or organization theory are considered as well (Radant, 2014;Radant, Colomo-Palacios, & Stantchev, 2014). This paper shows that the research community currently does not provide satisfactory answers for the problem of scarcity of talent and skill shortage in IT-departments.…”
Section: Discussionmentioning
confidence: 92%
“…Focusing on Europe, this scarcity of talent is threatening the ability to exploit the full potential of Big Data in the zone [12]. The cause may be current times of scarcity of talent in IT [6,7,24] or maybe the need of a new set of technical competences. In work environments, demand for Big Data expertise across a range of occupations saw significant growth in 2014 according to Forbes [8]; moreover, in this report, the author reported that there was a 123.60% jump in demand for Information Technology Project Managers with Big Data expertise, and an 89.8% increase for Computer Systems Analysts.…”
Section: Big Data As a Subjectmentioning
confidence: 99%